PENINGKATAN HASIL BELAJAR IPS DENGAN MODEL COOPERATIVE LEARNING TIPE PICTURE AND PICTURE DI SEKOLAH DASAR - Mardiyah, Ainul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The aim of this research is to improve student learning outcomes by using cooperative learning model of type picture and picture toward the fifth grade students in the SDN 04 Matua. This research uses qualitative and quantitative approaches. Those are research of a class act which was carried out by two cycles, and each cycle consists of four stages: planning, implementation, observation, and reflection. This learning model’s can improve student learning outcomes. Kata Kunci : hasil belajar, ilmu pengetahuan sosial, model cooperative learning tipe picture and picture